A comparative study on leaf, petiole and stem morphology of Araceae species - Nawi, Liliwirianis; Ayub, Nik Azlina; Mohamed Mohidin, Farah Shahanim; Rustam Affandy, Sarah Hanim; Mohd Zaki, Suhanom (Universiti Teknologi MARA, 2010)
This study examines the leaf, petiole and stem of 13 species of Araceae on the basis of their morphology. All the species represent three subfamilies: Monsteroideae, Pothoideae and Aroiodeae and consist of seven genera: Anthurium, Spathiphyllum, Monstera, Philodendron, Syngonium, Alocasia and Caladium. A dichotomous key that describes all the characteristics used in the identification of the Araceae species is also constructed.